Systematic review and meta-analysis protocol of impact of pharmacist-led antibiotic stewardship audit-feedback intervention - Duaa Salem Jawhar; Amer Hayat Khan; Khurshid Alam (MethodsX, 2025)
The rise of resistance to antibiotic agents continues to present a substantial challenge to healthcare systems. In response, antibiotic stewardship programs (ASPs) have been widely endorsed as a core strategy to promote the responsible use of antimicrobials and to curb the progression of antimicrobial resistance (AMR). Pharmacist-led audit and feedback interventions hold significant promise due to pharmacists' clinical expertise and direct role in optimizing antimicrobial prescribing. However, despite their potential, the current body of evidence evaluating the effectiveness of pharmacist-led audit and feedback within ASPs remains limited and fragmented. A clearer understanding of their impact is essential to inform policy decisions, support broader implementation, and enhance the overall effectiveness of stewardship efforts. This protocol has been registered with the PROSPERO under the registration number CRD420251036088. The review will be conducted in accordance with the PRISMA guidelines.A comprehensive search will be carried out across four major databases, and studies will be selected based on clearly defined inclusion and exclusion criteria. The risk of bias in the included studies will be assessed using Cochrane riak of bias assessment tools. Publication bias will be examined using funnel plots and Egger’s test. For the quantitative synthesis, a random-effects model will be employed. • This protocol outlines a rigorous plan for conducting a high-quality meta-analysis examining the impact of pharmacist-led audit and feedback interventions within antibiotic stewardship programs. • It details the full methodological framework, from topic selection through to the statistical approaches planned for data synthesis. • By publicly sharing our protocol through an academic publishing platform, we aim to promote transparency, invite constructive input, and contribute to raising the methodological standards for meta-analyses in the domain of antibiotic stewardship.